2014
DOI: 10.1136/jnnp-2013-307041
|View full text |Cite
|
Sign up to set email alerts
|

The impact and prognosis for dystonia in childhood including dystonic cerebral palsy: a clinical and demographic tertiary cohort study

Abstract: In this selective cohort, childhood dystonia is severe, presenting early before worsening without remission. Secondary dystonias spend a higher proportion of life living with dystonia and lower functional capacity. Despite referral bias, services offering neurosurgical interventions and health service planning agencies should understand the context and predicament of life with childhood dystonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
106
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 27 publications
3
106
0
1
Order By: Relevance
“…7 But for most children, dystonia exerts a significant, life-long reduction of activity and participation. 8,9 A recent large, UK, supra-regional, demographic study of the management of hypertonus in children reported that less than 8% of all referred dystonia cases improved: in fact dystonia severity in primary, secondary and heredodegenerative dystonias aetiologies respectively worsened in 60.2% or remained at best static in 31.5%. giving a bleak prognosis for spontaneous improvement.…”
Section: Dystoniamentioning
confidence: 95%
“…7 But for most children, dystonia exerts a significant, life-long reduction of activity and participation. 8,9 A recent large, UK, supra-regional, demographic study of the management of hypertonus in children reported that less than 8% of all referred dystonia cases improved: in fact dystonia severity in primary, secondary and heredodegenerative dystonias aetiologies respectively worsened in 60.2% or remained at best static in 31.5%. giving a bleak prognosis for spontaneous improvement.…”
Section: Dystoniamentioning
confidence: 95%
“…23 Children with dyskinetic CP, especially those with dystonia, tend to have more severe motor impairment and an increased likelihood of learning disability, epilepsy, and visual and hearing impairments. 15,20 Well-known etiological factors are hypoxic-ischemic encephalopathy (HIE), infection, and hyperbilirubinemia, 15 which preferentially affect the basal ganglia and thalamus. These areas are particularly vulnerable given the high metabolic demands of the peri-and neonatal developmental periods.…”
mentioning
confidence: 99%
“…3 Dyskinetic CP is the most common cause for acquired dystonia in childhood. 4 The clinical presentation can be very heterogeneous with a variety of underlying etiologies. Patients often present with a mixed movement disorder comprising dystonia and choreoathetosis, axial hypotonia, and sometimes coexisting spasticity leading to severe impairment in activities of daily living.…”
Section: Cerebral Palsymentioning
confidence: 99%